DEFICIENCY OF VITAMIN D IN PATIENT WITH PRIMARY HYPOTHYROIDISM AND AS RELATED RISK FACTOR FOR CARDIOVASCULAR DISEASES - Sura Sudad Sami; Fatima Ayad Nemeh; Maryam Ghassan Fakhry; Hala Thaer Kamal (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Hypothyroidism is believed to be associated with dyslipidemia and is considered a risk factor for the development of atherosclerotic cardiovascular diseases (ASCVD). Vitamin D, due to its steroid hormone action, retains cell function and controls the metabolism of lipids. Therefore, the present study was carried out to show the association of the risk factors of ASCVD. Cardiovascular disease (CVD) is caused by both clinical and subclinical hypothyroidism by disrupting healthy endothelial function by various mechanisms such as inflam- mation, triggering lipid disorders and oxidative stress. In the present study, a strong correlation was observed between increasing TSH and the parameters of lipid profile Hypothyroidism and hypovitaminosis D are known as inde-pendent risk factors for the development of cardiovascular diseases. Hypothyroidism and hypovitaminosis D are associated and correlated with total cholesterol, triglycerides, and low-density lipoprotein in Saudi patients. It is also recom- mended that vitamin D deficiency be checked in hypothyroid patients and that appropriate supplementation may be given if needed. Furthermore, for early detection and/or prediction of cardiovascular disease, screening of thyroid hormone and vitamin D levels should be undertaken at an early stage.